2009
DOI: 10.1007/s10265-009-0230-z
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype richness in refugial areas: phylogeographical structure of Saxifraga callosa

Abstract: This paper illustrates the phylogeographical structure of Saxifraga callosa in order to describe its genetic richness in refugial areas and to reconstruct its glacial history. S. callosa is a species spread throughout south-east France and Italy with a high distribution in the Maritime Alps. Four chloroplast microsatellite and AFLP markers were analyzed in populations of S. callosa. The size variants of all tested loci amount to 11 different haplotypes. Intrapopulational haplotype variation was found in two of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
1
29
1
Order By: Relevance
“…Ribotype abbreviations are given in Table 3 Grassi et al 2009). On the other hand, this phylogeographic pattern is not completely comparable with the genetic diversity observed for S. callosa and A. alpina within the Apuan Alps (Ansell et al 2008;Grassi et al 2009). Indeed, AFLP and haplotype markers supported the proposal that these two alpine species survived in a refugia within the Apuan Alps, whereas, for E. spinosa, there is no evidence of glacial refugia in the Apuan Alps.…”
Section: Divergence Time Estimationcontrasting
confidence: 78%
See 2 more Smart Citations
“…Ribotype abbreviations are given in Table 3 Grassi et al 2009). On the other hand, this phylogeographic pattern is not completely comparable with the genetic diversity observed for S. callosa and A. alpina within the Apuan Alps (Ansell et al 2008;Grassi et al 2009). Indeed, AFLP and haplotype markers supported the proposal that these two alpine species survived in a refugia within the Apuan Alps, whereas, for E. spinosa, there is no evidence of glacial refugia in the Apuan Alps.…”
Section: Divergence Time Estimationcontrasting
confidence: 78%
“…They were the primary refugia for numerous animal and plant species that later re-colonized the continent. In addition, the diversification of genetic lineages occurred among smaller range fragments within these refugial areas and within other small areas (Ansell et al 2008;Grassi et al 2009;Médail and Diadema 2009). Many endemic taxa inhabiting refugial areas were characterized by allopatric fragmentation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mean h value of the Sele population was slightly higher in comparison with that calculated by Salvini et al (2001) in the case of five populations of P. tremula distributed along the Italian peninsula (0.51 Vs 0.33). These moderately high level of both genetic variability and number of haplotypes with respect to the same P. tremula Italian populations [8 Vs 6 - (Salvini et al, 2001)] can possibly be attributed to the fact that the white poplar population here analysed is located in an area (the Cilento) considered as a glacial refugium and a hot spot of biodiversity for several angiosperm species (Cottrell et al, 2005;Fineschi & Vendramin, 2004;Grassi et al, 2009;Petit et al, 2002;Petit et al, 2003). The nSSR analysis carried out on the same population revealed that the expected heterozygosity was relatively high (He 0.460), but in accordance with those reported by Castiglione et al (2010) in the case of three populations distributed along the banks of three rivers in northern and central Italy and with that calculated by Lexer et al (2005) for two populations of P. alba (0.419 and 0.341), and two of P. tremula (0.466 and 0.483 -Lexer et al 2005).…”
Section: Discussionmentioning
confidence: 89%
“…(Grassi et al 2009) survived glacial age in refugia within the MLA too. The phylogeographical pattern based on molecular data of Euphorbia spinosa (Zecca et al 2011) supports the hypothesis of long-term separation of the north-western (Maritime Alps, Sardinia, Corsica, North Apennines) and south-eastern (South Apennines and Balkan area) lineages; together with the estimated divergence time this result suggests the survival of the species into at least two glacial refugia during the Quaternary glaciations.…”
Section: Historical Factorsmentioning
confidence: 99%